2018
DOI: 10.1111/jce.13447
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intracardiac thrombus formation prior to electrical cardioversion in respect to the mode of oral anticoagulation

Abstract: NOAC therapy seems favorable in the overall prevention of ICT, although this is likely to be caused by suboptimal VKA therapy control and differences in the overall health status between VKA and NOAC patients. ICT occurred even with effective OAC therapy suggesting individual TEE-guided cardioversion in patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Study characteristics and quality evaluation: Overall, 6,860 patients from 13 studies were included in the analysis, of which 3,683 patients were treated with NOACs and 3,177 patients were treated with VKAs [Schaeffer 2018;Reers 2016;Kawabata 2017;Wyrembak 2017;Kim 2013;Maddox 2013;Nagarakanti 2011;Barysienė 2017;Ţînţ 2017;Frenkel 2016;Gunawardene 2017;Somani 2014]. All patients were examined by TEE prior to cardioversion or catheter ablation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics and quality evaluation: Overall, 6,860 patients from 13 studies were included in the analysis, of which 3,683 patients were treated with NOACs and 3,177 patients were treated with VKAs [Schaeffer 2018;Reers 2016;Kawabata 2017;Wyrembak 2017;Kim 2013;Maddox 2013;Nagarakanti 2011;Barysienė 2017;Ţînţ 2017;Frenkel 2016;Gunawardene 2017;Somani 2014]. All patients were examined by TEE prior to cardioversion or catheter ablation.…”
Section: Resultsmentioning
confidence: 99%
“…One study indicated that among initiators of oral anticoagulation, direct-acting oral anticoagulants use was low [Essien 2020]. In this meta-analysis, we included studies that evaluated the efficacy of LAT/LAAT prevention between NOACs and VKAs in patients undergoing cardioversion [Schaeffer 2018;Barysienė 2017;Ţînţ 2017], or catheter ablation [Frenkel 2016;Gunawardene 2017;Somani 2014], or both [Reers 2016]. Additionally, some studies focus on the AF patients undergoing cardiac surgery, elective cardioversion, or catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the limitations that are intrinsic to a nonrandomized study, there are a few other issues to point out regarding the work of Schaeffer et al . First, there is no standardized grading system for spontaneous echo contrast.…”
mentioning
confidence: 99%
“…In this issue of the Journal of Cardiovascular Electrophysiology , Schaeffer et al. shed further light on the adequacy of NOAC versus vitamin K antagonist (VKA) as a means of anticoagulation by providing real‐world TEE data regarding the incidence of intracardiac thrombi and dense spontaneous echo contrast in patients who are about to be cardioverted . They found a significantly lower incidence of thrombus formation in patients on NOACs compared with patients taking VKA (2.5% vs. 5.3%, P = 0.019).…”
mentioning
confidence: 99%